Identification and Mapping of Readiness of Micro and Small Coffee Industry Cluster Development - Lya Aklimawati; Djoko Soemarno; Surip Mawardi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2015)
Cluster development of micro and small-scaled coffee industry is an effortto improve the economy of community by utilizing local resources. This studywas aimed to identify phase of cluster growth through determinant factors ofindustrial cluster growth; to assess a linkage between economy players in theindustrial cluster; and to identify strength, weakness, opportunity, and threat incoffee industry development. This research was carried out in Sumberwringin,Bondowoso District, East Java. Survey method through direct observation andinterviews were conducted in this study. Data collected included primary andsecondary data. Number of respondents were 25 industry players selected byjudgement sampling method. The data were analyzed by exploratory descriptivewith content analysis method. This research concluded that industrial clusterstudied was still in phase of formation and initiative (embryo) and its growthpattern followed Pattern III. Interrelationship between core industries has notbeen established, while linkage between core industries and supporting industrieshad already well-established. Strength and opportunity in coffee industrydevelopment included raw materials availability, market segment growth. Smalland micro enterprises credit facility, supporting facility, and labor availability.Constraints and threat faced by coffee industry included limited market access,in adequate machineries, limited working capital, raw materials quality, inconsistentproduct quality, credit claim, and competitors.